2015
DOI: 10.1016/j.ica.2014.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the synthesis and understanding of the iodo-bridged intermediate en route to the Pt(IV) prodrug satraplatin

Abstract: Mixed amine/ammine motifs are important features in newer generation platinum anticancer agents, including the Pt(IV) prodrug satraplatin. One synthetic route that can be used to access platinum molecules with such structures exploits the trans effect during NH3-mediated cleavage of iodo-bridged platinum(II) dimers of the form [Pt(Am)I(μ-I)]2, where Am is an amine. A clear picture of the nature of these dimers that is consistent with the reactivity they exhibit has remained elusive. Moreover, technical aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Silver acetate (369 mg, 2.21 mmol) was added to a solution of cis -[Pt­(NH 3 )­(CHA)­I 2 ] (673 mg, 1.19 mmol; CHA = NH 2 C 6 H 11 ) in 12 mL of DMF. After the mixture was stirred for 14 h at room temperature, precipitated AgI was filtered off and the filtrate was evaporated to give a brown oil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver acetate (369 mg, 2.21 mmol) was added to a solution of cis -[Pt­(NH 3 )­(CHA)­I 2 ] (673 mg, 1.19 mmol; CHA = NH 2 C 6 H 11 ) in 12 mL of DMF. After the mixture was stirred for 14 h at room temperature, precipitated AgI was filtered off and the filtrate was evaporated to give a brown oil.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays one of the most popular approaches to overcome these drawbacks is to use kinetically inert octahedral Pt­(IV) derivatives of the semilabile square-planar cisplatin. Pt­(IV) complexes are derived from Pt­(II) by oxidative addition, where two ligands are added to the axial positions. Their kinetic inertness minimizes unwanted extracellular interactions, but once inside the cancer cell the complex is reduced, releasing the original Pt­(II) drug as well as the two axial ligands (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon entry into the bloodstream, satraplatin undergoes reduction to give six distinct platinum­(II) species. Ammine­(cyclohexylamine)­dichloroplatinum­(II), derived from the loss of two acetate ligands, is the major metabolite and also exhibits the most potent anticancer activity. , In preclinical studies, satraplatin exhibited a better toxicity profile than cisplatin and showed activity in cisplatin-resistant human tumor cell lines . Similarly to cisplatin, satraplatin acts through formation of DNA cross-links, DNA distortion, and subsequent inhibition of DNA transcription and replication.…”
Section: Platinum(iv) Prodrugs That Release Classical Platinum(ii) An...mentioning
confidence: 99%
“…59 These include the second-generation clinical anticancer agents, carboplatin and nedaplatin, the third-generation platinum complexes, oxaliplatin and lobaplatin, and other cisplatin/transplatin analogues such as fatty amine ligands, planar heterocycle ligands, iminoether ligands, and so on. 1013 Initial structure–activity connection research proposes that the leaving groups, commonly chloride and two amine ligands in the platinum complexes, must be in a cis -configuration and that the corresponding trans -compounds are inactive. However, various trans -platinum compounds have been established as potential drugs, numerous researchers have published on trans -Pt compounds with in vitro growth inhibitory and in vivo antitumor properties.…”
Section: Introductionmentioning
confidence: 99%